2020
DOI: 10.1007/s42452-020-03414-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical studies on two-tiered MSE walls under seismic loading

Abstract: Mechanically Stabilized Earth (MSE) retaining walls, reinforced by the geogrids and using rigid segmental blocks as facing elements have extensively been used in recent past as an economic and sustainable solution for the earth retention. Nevertheless, in the case of a high retaining wall, tiered walls are preferred than a single-tier retaining wall due to their cost-effectiveness and more stability than single-tiered MSE walls. However, the behavior of tiered MSE retaining wall under dynamic loading is not ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The mechanism utilized for the transfer of forces between two dissimilar materials is simulated using an elastoplastic interface, bearing the interface coefficient values like 0.7 [24] and 0.8 [25] for geosynthetic-soil and geosynthetic-block interfaces, respectively. These are allocated at all the interfaces in this GRS wall and footing system.…”
Section: Materials Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism utilized for the transfer of forces between two dissimilar materials is simulated using an elastoplastic interface, bearing the interface coefficient values like 0.7 [24] and 0.8 [25] for geosynthetic-soil and geosynthetic-block interfaces, respectively. These are allocated at all the interfaces in this GRS wall and footing system.…”
Section: Materials Parametersmentioning
confidence: 99%
“…Moreover, taking a large number of elements for a given mesh becomes time taking procedure for the simulation. On account of the above, a sensitivity analysis is conducted to acquire the ideal number of elements desired for the mesh taken in the present analysis [24][25][27][28]. The overall number of elements is ranged from 2000 to 6000 with a successive increment of 1000 elements in each simulation.…”
Section: Materials Parametersmentioning
confidence: 99%
“…A sensitivity analysis was performed by varying the number of total elements in the mesh from 1000 to 10000 and it is found that 6000 elements were good enough for the considered mesh in the present study based on an observed outcome by varying the number of elements in the mesh (Fig. 2) [14,15,[34][35][36]. An incremental vertical uniformly distributed surcharge on the footing and a seismic horizontal acceleration on the body of the considered mesh is applied to investigate the behavior of footing under the effect of seismic loading.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…Soil reinforcement is a method to enhance the stability of the overall structure (e.g., bridge abutment, mechanically stabilized earth walls, etc.) by adopting the practices of the high tensile member below the foundation in the form of geosynthetics [27,34]. Over the past few decades, there are several innovative ground modification techniques such as reinforcing soils using geosynthetics that have been developed and widely adopted in the field.…”
Section: Introductionmentioning
confidence: 99%
“…in Built Environment frontiersin.org applying equilibrium equations that impose stress boundary conditions and no violation of the yield criteria. Note that OptumG2 has been employed in several previous works to perform various geotechnical stability problems (e.g.,Keawsawasvong and Ukritchon, 2019a;Keawsawasvong and Ukritchon, 2019b;Keawsawasvong and Ukritchon, 2020;Srivastava and Chauhan …”
mentioning
confidence: 99%